Soil bacterial community composition is altered more by soil nutrient availability than pH following long-term nutrient addition in a temperate steppe - Zhang, Hao; Jiang, Na; Zhang, Siyu; Zhu, Xiaoyu; Wang, Hui; Xiu, Weiming; Zhao, Jianning; Liu, Hongmei; Zhang, Haifang; Yang, Dianlin (Frontiers in Microbiology, 2024)
While above-ground biodiversity has been extensively studied, the response of soil microbial populations to nutrient enrichment remains unclear. Soil microorganisms serve as important indicators in shaping soil nutrient cycling processes and are typically sensitive to nutrient additions. For this, we employed a factorial combination design to examine the impact of nutrient additions on the composition and function of soil bacteria in a temperate steppe. Nitrogen addition promoted the growth of copiotrophic bacteria (Proteobacteria, Firmicutes, and Bacteroidota) but inhibited the growth of oligotrophic bacteria (Acidobacteria, Chloroflexi, and Verrucomicrobiota). Phosphorus addition alleviated phosphorus deficiency, resulting in a decrease in the abundance of phoDharboring bacteria (Actinobacteria and Proteobacteria). Significant enhancement of soil bacterial alpha diversity was observed significantly only in treatments with added phosphorus. Changes in NO3--N, NH4+-N, available phosphorus, and dissolved organic carbon resulting from nutrient addition may have a greater impact on microbial community structure than changes in soil pH caused by nitrogen addition. Moreover, nutrient addition may indirectly impact microbial ecological function by altering nutrient availability in the soil. In conclusion, our study suggests that soil nutrient availability, particularly available phosphorus, affects soil bacterial communities and potentially regulates the biogeochemical cycles of soil ecosystems.